HUBUNGAN PENGETAHUAN KOREKSI BENTUK WAJAH DENGAN HASIL BELAJAR PRAKTEK RIAS WAJAH PADA MAHASISWI ANGKATAN 2014 PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN JURUSAN KESEJAHTERAAN KELUARGA FT UNP - Yarizqi, Tartila; Rostamailis, Rostamailis; Astuti, Murni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to reveal the relationship between facial shapecorrection knowledge with practical learning outcomes makeupeducation student of Makeup and Beauty Family Welfare Departmentof the Faculty of Engineering, State University of Padang. This studyuses a quantitative method with a correlation type approach, with apopulation of 37 people. While the samples are all made in the samplepopulation which is 37 student class of 2014 or Total Sampling.Instrument research using a questionnaire (questionnaire) in the formof objective test that has been tested for validity and reliability. Dataanalysis was performed using the percentage level of achievement ofthe respondents (TCR), correlation using Product Moment formulafollowed by t test for basic decisions accepted hypothesis. The resultsshowed that the percentage achievement of respondents KnowledgeCorrection Face Shape variable (X) is 80% with high and variablecategories of practice learning outcomes makeup (Y) was 77% withmedium category. The relationship between the two variables are at ascore of 0760 with interpretation strong relationships, t test stating thatthe alternative hypothesis which says There is a positive andsignificant relationship between knowledge Correction Face Shapewith Learning Outcomes Practice Student Makeup Makeup Educationstudy program and Beauty KK FT UNP